Cardiovascular Consequences of Unfair Pay - Armin Falk; Ingo Menrath; Pablo Emilio Verde; Johannes Siegrist (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
This paper investigates physiological responses to perceptions of unfair pay. In a simple principal agent experiment agents produce revenue by working on a tedious task. Principals decide how this revenue is allocated between themselves and their agents. In this environment unfairness can arise if an agent's reward expectation is not met. Throughout the experiment we record agents' heart rate variability. Our findings provide evidence of a link between perceived unfairness and heart rate variability.The latter is an indicator of stressrelated impaired cardiac autonomic control, which has been shown to predict coronary heart diseases in the long run. Establishing a causal link between unfair pay and heart rate variability therefore uncovers a mechanism of how perceptions of unfairness can adversely affect cardiovascular health. Wefurther test potential adverse health effects of unfair pay using data from a large representative data set. Complementary to our experimental findings we find a strong and highly significant association between health outcomes, in particular cardiovascular health, and fairness of pay.
Keywords: D3; D63; I14; C91; 330; Fairness; social preferences; inequality; heart rate variability; health; experiments; SOEP; Soziales Verhalten; Lohnniveau; Gerechtigkeit; Herzkrankheit; Test